2022
DOI: 10.1039/d1tc04257b
|View full text |Cite
|
Sign up to set email alerts
|

Cocrystal engineering for constructing two-photon absorption materials by controllable intermolecular interactions

Abstract: The intermolecular interactions of cocrystals can be controlled via selecting the donors and acceptors, and then the TPA properties can be selectively adjusted, promoting the development of TPA materials prepared via cocrystal engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…The turning point occurred when TCNQ was inserted. The considerable energy difference between the HOMO of TP-TBDA and the LUMO of TCNQ resulted in the generation of a charge-transfer effect from TP-TBDA to TCNQ, and then the molecular orbitals shifted greatly . The HOMO was distributed on the donor TP-TBDA, and the LUMO was distributed on the acceptor TCNQ; at the same time, in the excited state of TP-TBDA@TCNQ, the decreased overlap of S 1 molecular orbital caused the t index to increase to 5.424 Å, which indicated that the assembly of the guest in TP-TBDA enables the electron and hole to separate more thoroughly. In the meantime, the LUMO level and the HOMO–LUMO band gap of TP-TBDA@TCNQ were both reduced compared to those of TP-TBDA, manifesting that the addition of guest can promote the injection of electrons at the cathodic potential and strengthen the charge transfer between the COF host and guest, thereby promoting the ECL.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The turning point occurred when TCNQ was inserted. The considerable energy difference between the HOMO of TP-TBDA and the LUMO of TCNQ resulted in the generation of a charge-transfer effect from TP-TBDA to TCNQ, and then the molecular orbitals shifted greatly . The HOMO was distributed on the donor TP-TBDA, and the LUMO was distributed on the acceptor TCNQ; at the same time, in the excited state of TP-TBDA@TCNQ, the decreased overlap of S 1 molecular orbital caused the t index to increase to 5.424 Å, which indicated that the assembly of the guest in TP-TBDA enables the electron and hole to separate more thoroughly. In the meantime, the LUMO level and the HOMO–LUMO band gap of TP-TBDA@TCNQ were both reduced compared to those of TP-TBDA, manifesting that the addition of guest can promote the injection of electrons at the cathodic potential and strengthen the charge transfer between the COF host and guest, thereby promoting the ECL.…”
Section: Results and Discussionmentioning
confidence: 99%
“…25 Moreover, the facile ICT between the donor and acceptor can be another approach to increase the d 2PA value. [98][99][100] However, a greater extent of ICT reduces the F F and hence d 2PA , which directly affects the twophoton brightness (Fig. 12).…”
Section: Small Organic-based Two-photon Fluorescent Probesmentioning
confidence: 99%
“…20,21 More importantly, the noncovalent intermolecular interactions between D-A molecules lead to tailored energy levels, providing a possibility for directional modulation of the optical properties. [22][23][24][25] For instance, the common intermolecular charge transfer (CT) interactions between D and A molecules can generate efficiently narrowed band gaps within cocrystals. 26 Moreover, the strong D-A interactions usually result in the forbidden electronic transitions of the CT state, which promotes non-radiative transition.…”
Section: Introductionmentioning
confidence: 99%